Association between School Membership and Substance Use among Adolescents - Gaete, Jorge; Rojas, Graciela; Fritsch, Rosemarie; Araya, Ricardo (Frontiers in Psychiatry, 2018)
Background: Substance use among adolescents is a major problem worldwide, producing many health and economic consequences. Even though there are well known personal, familial, and social factors associated with drug use, less is known about the effect of school-related factors. School membership is a recognized variable affecting academic performance among students; however, its effect on substance use is less understood. Aims: The primary aim of this study was to explore the association between school membership and cigarette, alcohol and cannabis use among a representative sample of secondary students from municipal state-funded schools in Santiago of Chile, and secondly, to test the hypothesis that depressive or anxiety symptoms mediate this association. Methods: A total of 2508 students from 22 state funded schools in Santiago, Chile, answered a questionnaire. This instrument included an abbreviated version of the Psychological Sense of School Membership, questions regarding the use of alcohol, tobacco and cannabis and scales of psychological functioning (depression, anxiety, self-concept and problem-solving). The association analyses were performed using adjusted regression models for each outcome using all independent variables while controlling for gender and age. For the mediation effect, a combination of ordinary least square and logistic regression analyses were conducted. Results: There was an association between a strong psychological sense of school membership and low risk for smoking (OR 0.57; 95% CI 0.46-0.72), drinking (0.65; 95% CI: 0.51-0.83) and cannabis use (0.52; 95% CI 0.37-0.74). We also found that depressive and anxiety symptoms do not fully mediate the association between school membership and any substance use, and 73% of this effect in the case of smoking, 80% in the case of drinking, and 78.5% in the case of cannabis use, was direct. Conclusions: This is the first study in Latin America exploring the association between school membership and substance use among secondary students. School membership seems to be an important and independent factor to be included in preventive interventions. Therefore, these results support future research aiming to test interventions at increasing the sense of school membership to prevent substance use among adolescents.